Mathematical Formula Recognition and Transformation to a Linear Format Suitable for Vocalization - Nazemi, Azadeh; Murray, Iain (Engg Journals Publications, 2013)
Students with vision impairment encounter barriers in studying mathematics particularly in higher education levels. They must have an equal chance with sighted students in mathematics subjects. Making mathematics accessible to the vision impaired users is a complicated process. This accessibility can be static or dynamic, in static accessibility the user is presented with a representation of the entire mathematic expression passively such as using Braille, dynamic accessibility allows the user to navigate the mathematical content in accordance with its structure interactively such as audio format [1]. MATHSPEAK is an application that accepts objects described in LaTeX and converts it to a linear or sequential representation suitable for vocalization, describing functions to people with severe vision impairment. MATHSPEAK provides interactive dynamic access to mathematic expressions by rendering them to audio format. This paper describes a method to create plain text from images of mathematical formulae and convert this text to LaTeX which is used in the earlier developed algorithm, “MATHSPEAK”.